2019
DOI: 10.3390/nano9111524
|View full text |Cite
|
Sign up to set email alerts
|

Bouncing Dynamics of Impact Droplets on the Biomimetic Plane and Convex Superhydrophobic Surfaces with Dual-Level and Three-Level Structures

Abstract: Reducing the contact time of a water droplet on non-wetting surfaces has great potential in the areas of self-cleaning and anti-icing, and gradually develops into a hot issue in the field of wettability surfaces. However, the existing literature on dynamic behavior of water drops impacting on superhydrophobic surfaces with various structural shapes is insufficient. Inspired by the microstructure of lotus leaf and rice leaf, dual-level and three-level structures on plane and convex surfaces were successfully fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…For the treatment with added surfactants, the retention of Fluo solution with AEO-4 was slightly lower. Based on the properties of the solution containing the surfactant, it is concluded that for spray droplets with no obvious bouncing behavior and good adhesion performance, 47 we need to consider the problem of pesticide liquid loss in practical applications and try to improve its utilization rate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For the treatment with added surfactants, the retention of Fluo solution with AEO-4 was slightly lower. Based on the properties of the solution containing the surfactant, it is concluded that for spray droplets with no obvious bouncing behavior and good adhesion performance, 47 we need to consider the problem of pesticide liquid loss in practical applications and try to improve its utilization rate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The aforementioned ice-proof strategy only delays the accumulation of condensed droplets on the surface, [150][151][152] it does not fundamentally solve the problem of surface ice accumulation. Thus, anti-icing strategies by promoting the bouncing of droplets on superhydrophobic surfaces have attracted increasing attention.…”
Section: Droplets Bouncing and Sheddingmentioning
confidence: 99%
“…Reducing the contact time of water droplets on non-wetting surfaces has excellent potential in the field of anti-icing, gradually developing into a hot topic in the field of wetting surfaces. Lian et al 151 used aluminum alloy steel wire electrical discharge machining technology to successfully prepare a bionic plane and convex surface with a double-layer and three-layer structure, and then sprayed hydrophobic nanoparticles to achieve excellent superhydrophobic properties. By comparing the bounce behavior of water droplets on the surface of these different square grooves, the best structure spacing, width and height influence on the contact time were obtained.…”
Section: Droplets Bouncing and Sheddingmentioning
confidence: 99%
“…This exhibits anisotropic hydrophobicity. The surface of rice leaves [17][18][19] is also an anisotropic hydrophobic surface. It has a sub-millimeter groove array structure of large size.…”
Section: Introductionmentioning
confidence: 99%